An Error Analysis of Descriptive Writing Based on Surface Strategy Taxonomy Made by the Eight Grade Students of SMP N 6 Kebumen in the Academic Year of 2019 / 2020 - Firharmawan, Hastri; Komariyah, Ida (English Education and Literature Journal (E-Jou), 2021)
To support success in the future, the mastery of writing is significant for school students. However, acquiring this ability may take time because students have to learn to minimize errors. This research aims to describe the students’ errors in their writing of descriptive texts and finding out the degree of the errors made by the eight grade students of SMP N 6 Kebumen in the academic year of 2019 / 2020. The writer used descriptive qualitative method in conducting the study. The research involved 32 students of grade VIII in the academic year of 2019 / 2020 at SMP N 6 Kebumen as participants that were selected by purpose. Data in this research were in the forms of words and sentences showing the students’ writing ability of descriptive texts taken from the worksheet documents done by the students. The writer analysed the documents by using the surface strategy taxonomy proposed by Dulay et.all. (1982:152). Data validity was gained by using investigator triangulation. It is how examination of the credibility of the data is done by making use of other observers for checking the degree of trust of the data.The results of the research showed that there had been found 123 items of errors in the descriptive writings made by the students of grade VIII at SMP N 6 Kebumen in the academic year of 2019/2020. These errors consisted of four types. They covered errors of ommision, errors of misformation, errors of addition, and errors of misordering. The sequence of the errors from the most dominant type to the least one was errors of misformation (61%), errors of omission (20%), errors of addition (15%), and errors of misordering (4%). This research was described the students’ errors in writing descriptive texts. Accordingly, this possibly helps students correct their errors to produce better writing later. Keywords: Error analysis, descriptive writing, surface strategy taxonomy